Knowledge, Attitude and Practice of Fascioliasis in Abattoirs: Implication for Public Health in Osun State, Nigeria - Ige, Grace Oluwabukola; Surakat, Olabanji Ahmed Surakat; Rufai, Akinlabi Mohammed; Fasasi, Kamilu Ayo; Abuh, Ojomona Oboro Abuh; Dauda, Oluwadamilare Ganiu; Azeez, Dauda Ishola; Adeshina, Quadri Olusegun; Iwalewa, Zarat Oyindamola; Jokanola, Glory Blessing; Awoniyi, Ilias Olufemi; Babalola, Ayodele Samuel; et al. (FUDMA Journal of Sciences, 2026)
Fascioliasis is a livestock parasite causing significant economic and public health concerns. A cross-sectional survey of 225 butchers and meat sellers in Osun State assessed livestock sources, inspection practices, treatment methods, snail control, and disease perceptions. Most respondents were male (97.3%), aged 30–60 (68.9%), and educated to at least secondary level (68.4%). Cattle, the sole livestock slaughtered, originated from neighboring states (43.6%) or combined neighboring and imported sources (33.8%). Veterinary pre-slaughter inspection was reported by 98.7%, and post-slaughter liver inspection by 96.9%. Fascioliasis was observed occasionally (57.3%) or rarely (41.3%), causing liver condemnation in up to 30% of cases. Detection relied on visual signs: enlarged/damaged livers, poor body condition, and anemia. While 73.8% of livestock received pre-slaughter deworming, schedules were irregular. Snail control measures were uncommon on farms and at abattoirs. All respondents recognized the economic impacts of fascioliasis, including liver condemnation, reduced meat quality, and lower market value. Public health risks were acknowledged, with organ condemnation acting as the primary preventive measure. Most workers (90.2%) had received training, and 90.2% were willing to undergo further training. The study demonstrates good awareness and positive attitudes toward fascioliasis, but preventive practices remain inadequate. To reduce disease burden and associated losses, the study recommends strengthened education, regular deworming programs, and targeted snail control strategies.